RogueLibras: A Serious Game to Learn Brazilian Sign Language Vocabulary - de Souza, Alexandre dos Anjos [UNESP]; Pereira, Leonardo Tórtoro [UNESP]; Oliveira, Wilk; Ranieri, Caetano Mazzoni [UNESP] (Association for Computing Machinery (ACM), 2025)
Beyond 400 million people have moderate or complete hearing loss and typically communicate with sign language. Acquiring this language can be challenging due to the lack of easily accessible learning materials. Facing this problem, we present RogueLibras, a Roguelike Deck builder serious game that uses the genre’s mechanics and gameplay to learn sign language and can be played even on low-end computers. We tested the game with 30 hearing anonymous participants using an ad hoc questionnaire that included a set of questions administered both before and after the participants played the game to evaluate whether participants learned any LIBRAS signs. Their score significantly improved when comparing knowledge of Libras’ signs before and after playing. The study contributes to discussing sign language education through a card-based game designed for low-end computers.